2019
DOI: 10.3390/cancers11091322
|View full text |Cite
|
Sign up to set email alerts
|

A Tunable Nanoplatform of Nanogold Functionalised with Angiogenin Peptides for Anti-Angiogenic Therapy of Brain Tumours

Abstract: Angiogenin (ANG), an endogenous protein that plays a key role in cell growth and survival, has been scrutinised here as promising nanomedicine tool for the modulation of pro-/anti-angiogenic processes in brain cancer therapy. Specifically, peptide fragments from the putative cell membrane binding domain (residues 60–68) of the protein were used in this study to obtain peptide-functionalised spherical gold nanoparticles (AuNPs) of about 10 nm and 30 nm in optical and hydrodynamic size, respectively. Different h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 85 publications
(118 reference statements)
0
15
0
Order By: Relevance
“…To note, the size, shape, and surface functional groups are pivotal to drive bioavailability, uptake, subcellular distribution, metabolism, and degradation of the nanoparticle. In particular, according to many reports, gold nanoparticles in the size range of 4-18 nm, upon capping with agents like citrate, cysteine, glucose, and biotin, are nontoxic in several cell lines, including leukemia cells (nanoparticle concentration up to 200 micromolar (µM), neuroblastoma and brain glioblastoma (nanoparticle concentration lower than 10 nanomolar [57,58]), and human immune system cells (nanoparticle concentration up to 100 micromolar [104]).…”
Section: Biological Characterization Of Go and Go@aunp Nanocomposite mentioning
confidence: 99%
See 1 more Smart Citation
“…To note, the size, shape, and surface functional groups are pivotal to drive bioavailability, uptake, subcellular distribution, metabolism, and degradation of the nanoparticle. In particular, according to many reports, gold nanoparticles in the size range of 4-18 nm, upon capping with agents like citrate, cysteine, glucose, and biotin, are nontoxic in several cell lines, including leukemia cells (nanoparticle concentration up to 200 micromolar (µM), neuroblastoma and brain glioblastoma (nanoparticle concentration lower than 10 nanomolar [57,58]), and human immune system cells (nanoparticle concentration up to 100 micromolar [104]).…”
Section: Biological Characterization Of Go and Go@aunp Nanocomposite mentioning
confidence: 99%
“…Plasmonic properties of gold nanoparticles (AuNPs) are commonly exploited in biomedical imaging and biosensing [24,52], in biochemistry [53], photothermal therapy [54] and anti-angiogenic applications [55][56][57][58] as a result of the easily tunability of the surface plasmon (SP) band by varying size, shape, or by gold surface modification [59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, graphene-based materials tailored at their surface with biomolecules may considerably change their response at the biointerface (Zhang et al, 2013;He et al, 2017). In general, the surface "decoration" of nanomaterials by peptide molecules is a useful approach to increase their biocompatibility by a biomimetic approach as well as to enhance their biological effects (Forte et al, 2014;Naletova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nanotechnologies can help fighting against angiogenesis, a phenomenon in which blood vessels that irrigate GBM tumors are more numerous and abnormal compared with normal blood vessels, supporting the progression, infiltration and migration of GBM cells. This can be achieved by nano-drugs promoting the growth of new non-angiogenetic vessels [110], or neutralizing certain angiogenetic growth factors including members of the vascular endothelium growth factor (VEGF) family [111], Angiogenin [112], or Tetrac [113], in particular, to improve the results obtained with non-nanoparticulate formation containing certain anti-angiogenic compounds such as anti-VEGF that failed to show a therapeutic benefit in clinical trials (phase III) [114]. More specifically, it has been demonstrated that complexes formed by Angiogenin (ANG) and gold nanoparticles (AuNPs) resulted in anti-angiogenic behavior towards GBM tumor cells [112].…”
mentioning
confidence: 99%
“…This can be achieved by nano-drugs promoting the growth of new non-angiogenetic vessels [110], or neutralizing certain angiogenetic growth factors including members of the vascular endothelium growth factor (VEGF) family [111], Angiogenin [112], or Tetrac [113], in particular, to improve the results obtained with non-nanoparticulate formation containing certain anti-angiogenic compounds such as anti-VEGF that failed to show a therapeutic benefit in clinical trials (phase III) [114]. More specifically, it has been demonstrated that complexes formed by Angiogenin (ANG) and gold nanoparticles (AuNPs) resulted in anti-angiogenic behavior towards GBM tumor cells [112]. Nano-formulated Tetrac led to devascularization of GBM tumor vessels (i.e., a 95% loss of tumoral vascularity in mice bearing GBM xenografts) [103], while graphite/graphene nanoparticles yielded a decreased concentration of intracellular ROS and RNS, hence affecting a series of mechanisms involved in the promotion of angiogenesis [115].…”
mentioning
confidence: 99%